Future home of the living god [compact disc, unabridged] : a novel - Erdrich, Louise (Harper Audio, 2017)
The world as people know it is ending. Evolution has reversed itself, affecting every living creature on earth. Science cannot stop the world from running backwards, as woman after woman gives birth to infants that appear to be primitive species of humans. Thirty-two-year-old Cedar Hawk Songmaker, adopted daughter of a pair of big-hearted, open-minded Minneapolis liberals, is as disturbed and uncertain as the rest of America around her. But for Cedar, this change is profound and deeply personal. She is four months pregnant. Though she wants to tell the adoptive parents who raised her from infancy, Cedar first feels compelled to find her birth mother, Mary Potts, an Ojibwe living on the reservation, to understand both her and her baby's origins. As Cedar goes back to her own biological beginnings, society around her begins to disintegrate, fueled by a swelling panic about the end of humanity.